Motivational factors, learning strategies and competencies in natural sciences - Torres López, Ángela Yohana; Torres-Rojas, Ingrid Selene; Camelo Mendoza, Rossana Ninoska (Gaceta Médica de Caracas, 2023)
It is analyzed the relationship between the motivational factors with the learning strategies that the students of the Department of Cauca in Colombia present in front of the basic standards of competencies in Natural Sciences. A non-experimental study was carried out with a quantitative approach, correlational type of study, and cross-sectional study time, with 423 participants. As instruments, the EDAOM, EMPA questionnaires, and the results of the basic standards of competencies in natural sciences according to the ICFES tests were applied. The findings indicate that motivation is not the determining factor for the low results obtained in the ICFES, but learning strategies are, so it is necessary to devise and contribute to creating these to obtain better student results.